Development of aptamer-based magnetic separation with PCR for Salmonella spp. detection and evaluation of nanocarbon aptasensor / Anis Nadyra Ahmad Zifruddin - Anis Nadyra, Ahmad Zifruddin (2018)
Foodborne illness is a major concern worldwide due to its impacts towards health, economics and society. One of the major foodborne diseases is salmonellosis that is caused by the members of the species Salmonella enterica. Even though culture method is the gold standard for pathogen detection, this method is too time-consuming and laborious. Therefore, many alternative methods have been developed to increase sensitivity, specificity and speed of detection. Foodborne pathogens detection involves various aspects which are sample preparation, isolation and detection. The objectives of the study were to improve the food sample preparation by using DNA aptamer magnetic separation (AMS) and evaluate the sensitivity and specificity of an aptamer-based biosensor (aptasensor) for Salmonella detection. In the first part of this study, biotinylated aptamer was coupled with the streptavidin magnetic beads and then used to isolate whole Salmonella cells, followed by detection using PCR targeting the invA gene. The limit of the detection of the AMS-PCR was 100 CFU/ml which was 10 times more sensitive than using PCR (103 CFU/ml) alone. The DNA aptamer could differentiate ten different Salmonella serovars without any cross-reactivity with other non-Salmonella spp. This AMS was also evaluated in naturally contaminated food samples (n = 14). The results showed that the use of AMS could reduce the detection time of Salmonella to 6 to 7 hours as compared to the conventional methods (pre-enrichment, enrichment, selective plating steps) which took 2 to 3 days. In the second part of this study, the sensitivity and specificity of the amino-modified aptasensor were determined. The aptasensor was previously developed by using carbon nanotube (CNT) deposited ITO substrate. The sensor conductivity and behaviour were determined by using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) using the AUTOLAB electrochemical instrument. When the aptasensor was exposed to Salmonella cells, the resistance increased, indicating the binding between Salmonella and the aptamer. The linear relationship between the peak of the current and different scan rates indicated the stability of the aptasensor. For sensitivity test, the aptasensor was exposed to different concentrations (5.5 101 to 106 CFU/ml) of Salmonella and showed its limit of detection at 55 CFU/ml. When the aptasensor was exposed to non-Salmonella cells (Staphylococcus aureus, Vibrio parahaemolyticus and E. coli), it did not show any cross-reactivity. Compared with culture method, this aptasensor could rapidly detect the Salmonella cells within one hour. In conclusion, the use of AMS with PCR could concentrate the bacterial cells in the initial food preparation and helped to reduce the total detection time of Salmonella in food samples. The aptasensor was shown to be rapid, specific and sensitive and could be further developed for Salmonella detection.